2018
DOI: 10.14712/23363177.2015.42
|View full text |Cite
|
Sign up to set email alerts
|

Do Student Teachers Attend to Mathematics Specific Phenomena when Observing Mathematics Teaching on Video?

Abstract: This article describes the results of an investigation into pre-service teachers' ability to notice mathematics specific phenomena in a lesson observed on a video recording. Thirty mathematics education students' written analyses of a viewed lesson were subjected to a selective content analysis. The results of both qualitative and quantitative nature conform with earlier research on pre-service teachers' lesson analyses and, in addition, bring detailed report not only on the participants' ability to notice but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 8 publications
1
6
0
3
Order By: Relevance
“…This again confirms our previous results (Vondrová & Žalská, 2012). Although there were opportunities for noticing a teacher's mathematical errors or misrepresentations in all three videos, only a very small proportion of students (13%) noticed at least one of these and only two of the 58 students watching the video commented on a moment where the teacher's incorrectness was an important feature of the lesson, possibly hindering pupils' understanding of the content taught.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This again confirms our previous results (Vondrová & Žalská, 2012). Although there were opportunities for noticing a teacher's mathematical errors or misrepresentations in all three videos, only a very small proportion of students (13%) noticed at least one of these and only two of the 58 students watching the video commented on a moment where the teacher's incorrectness was an important feature of the lesson, possibly hindering pupils' understanding of the content taught.…”
Section: Discussionsupporting
confidence: 89%
“…The presented study is a continuation of our previous study (Vondrová & Žalská, 2012), in which we were able to report the results of a detailed examination of 30 students' written analyses of a video recording of one full mathematics lesson. Overall, we confirmed that although the group of participants paid attention to issues of general pedagogy and classroom management, they did not tend to notice and comment on even prominent aspects related to mathematical content, such as a carefully devised series of tasks that the teacher in the video used to introduce new mathematical content, or the mathematics content contained in individual pupil-teacher interaction.…”
Section: Our Previous Workmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been suggested that teachers' decisions are impacted by school culture, the teacher's mathematical knowledge and their knowledge of mathematics teaching, the teaching situation, goals, learning outcomes, teacher's experience, and their beliefs and values Jacobs et al 2010). Investigations have also related decision-making processes in terms of teachers' internal knowledge, beliefs, attitudes, and practices (Bartlett 1932;Fisher et al 2014;Vondrová and Žalská 2012). inferred decision-making to be basically influenced by values.…”
Section: Teacher Noticing Decision-making and Teacher Valuesmentioning
confidence: 99%
“…Teachers' values (Bishop 2008a, pp. 191-203) and teachers' noticing (Vondrová and Žalská 2012) depend, at least to some extent, on the lesson content. In this study, the notion of regular polygons was the focus for all class groups.…”
Section: The Study Designmentioning
confidence: 99%